Pelatihan Dan Pengembangan Sdm Desa Dalam Pemanfaatan Limbah Kulit Nenas - Kiki Joesyiana; Asepma Hygi Prihastuti; Sri Wahyuni; Annesa Adriyani; Sri Wahyuni (Jurnal Pengabdian Masyarakat Madani, 2022)
Riau is included in the 5 largest pineapple producing provinces, with total pineapple production in 2020 as much as 214,277 tons. Rimbo Panjang Village is one of the pineapple producing villages in Kampar Regency, Riau Province. Around 48% of the people make a living as pineapple farmers, where currently the productive pineapple plantation is approximately 6000 ha with a total production of fresh pineapples of almost 7 tons per day in the harvest season. The pineapple harvest is then resold or processed to produce other products, such as pineapple chips, pineapple diamonds, pineapple lunkhead and pineapple syrup. From the pineapple fruit production, only the pulp is used, so that pineapple skin waste arises. To take advantage of the pineapple skin, training and development of human resources in Rimbo Panjang Village was held in utilizing pineapple skin into organic fertilizer. Based on the questionnaire distributed to the training participants, it was stated that the material provided was in accordance with the participants needs and it was hoped that there would be ongoing training for the further development of village human resources. Keywords: Training, Human Resources, Pineaplle Skin.